2001
DOI: 10.1021/jp011134h
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Nonlinear Optical Response in Zwitterionic Molecules:  A Computational Study on the Role of Orbital Interactions through σ Bonds

Abstract: Ab initio coupled perturbated Hartree-Fock calculations, using 6-31G** basis sets, on a heterocyclic zwitterionic molecule with a σ-spacer between the donor and the acceptor ring shows a static first hyperpolarizability ( 0 ) of around 240 × 10 -30 esu. Substitution of electron withdrawing functional groups, such as NO 2 , on the acceptor ring of this molecule enhances the 0 value to around 3960 × 10 -30 esu. Studies on various such zwitterionic molecules demonstrate the importance of π-σ orbital mixing (throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
64
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 40 publications
1
64
0
Order By: Relevance
“…Bhanuprakash and coworkers [18,19] have studied the NLO activity in some nonconjugated 3D triazine derivatives from both experiment and theoretical calculation. Moreover, Bhanuprakash and coworkers [20] systematically studied the role of orbital interactions through -bonds on enhanced NLO response in zwitterionic molecules. Jin et al [21] have synthesized novel crosslinkable polymers for secondorder nonlinear optics using palladium-catalyzed carbon-carbon coupling reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Bhanuprakash and coworkers [18,19] have studied the NLO activity in some nonconjugated 3D triazine derivatives from both experiment and theoretical calculation. Moreover, Bhanuprakash and coworkers [20] systematically studied the role of orbital interactions through -bonds on enhanced NLO response in zwitterionic molecules. Jin et al [21] have synthesized novel crosslinkable polymers for secondorder nonlinear optics using palladium-catalyzed carbon-carbon coupling reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The measurement of 2PA cross-sections is performed for three solvents (chloroform, dimethyl formamide, and dimethyl sulfoxide) using the Z-scan technique. [39,40,42,67,80,[84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100] The spectroscopic studies of RD are mainly focused on the behavior of its long-wavelength CT absorption band in a variety of media to obtain E T (30) and/or E T N values. To unravel the solvent dependence of the 2PA cross-section, the electronic structure of RD is determined using a hybrid quantum mechanics/molecular mechanics (QM/MM) approach, in which polarization between the solute and solvent is taken into account by using a self-consistent scheme in the solvent polarization.…”
Section: Introductionmentioning
confidence: 99%
“…The authors repeatedly indicated the possible connections between their findings and the nonlinear optical (NLO) properties for this class of compounds without making any calculations. It is well established, however, that the NLO properties, studied in detail for betaine dyes on purely theoretical basis during the last decade [2][3][4][5][6][7][8], depend crucially on the geometry of the so-called pushpull systems which, in turn, can be analyzed in terms of the bondlength alternation (BLA) parameter [9][10][11]. The results presented by Perpète et al may serve here as an excellent example that the electron correlation (EC) significantly affects the geometry and the wavefunction [12].…”
Section: Introductionmentioning
confidence: 99%